Use of Modern Cryomethods in Combined Surgical Treatment of Patients with Purulent Chronic Wounds - Goltsev, Kyrylo; Kryvoruchko, Igor; Goltsev Аnatoliy; Parkhomenko, Kyrylo; Horoshun, Eduard (Problems of Cryobiology and Cryomedicine, 2021)
The paper considers the possibilities of using in medical practice various cryomethods and techniques of cryopreservation of biological objects to treat the patients with purulent chronic wounds (PCW). The variety of methods and approaches to apply cold in medical practice: general and local cryotherapy, cryosurgery etc. has been emphasized. As a result of using each of these methods, regenerative processes begin, which promote the healing of PCW. Particular attention is paid to cryotechniques, ensuring the preservation of cord blood at low temperatures. Cord blood cells and serum have been shown to have immune modulatory and trophic-stimulating therapeutic effects, that is extremely important when treating the patients with PCW. The issue of combined use of cord blood serum and innovative vacuum therapy for the patients with PCW has been considered. Probl Cryobiol Cryomed 2021; 31(2): 109–115